Sam's fishing adventure - Russell, Monique, 1991- (Thuringowa, Qld. : Black Ink Press, 2010)
Grandfather's adventures with his family, as a child living on a Torres Strait Island, are retold and brightly illustrated by a young student teacher. Ages 5+.
For pre-school age.
Keywords: Literature and stories - Juvenile; Literature and stories - Fiction; Children - Childhood; Fishing; Torres Strait Islands (Qld TSI SC54, SC55-05); Muralag / Prince of Wales Island (Qld TSI SC54-11)